Half Moon Bay : a novel - Kellerman, Jonathan; Kellerman, Jesse (Kellerman, Jonathan. Clay Edison series., 2020)
"Deputy coroner Clay Edison discovers that buried secrets can be deadly in this riveting thriller from a father-son team of bestselling authors who write "brilliant, page-turning fiction" (Stephen King). Deputy Coroner Clay Edison has his hands full. He's got a new baby who won't sleep. He's working the graveyard shift. And he's trying, for once, to mind his own business. Then comes the first call. Workers demolishing a local park have made a haunting discovery: the decades-old skeleton of a child. But whose? And how did it get there? No sooner has Clay begun to investigate than he receives a second call--this one from a local businessman, wondering if the body could belong to his sister. She went missing fifty years ago, the man says. Or at least I think she did. It's a little complicated. And things only get stranger from there. Clay's relentless search for answers will unearth a history of violence and secrets, revolution and betrayal. Because in this town, the past isn't dead. It isn't even past. It's very much alive. And it can kill"--